Move contrast X-ray imaging reveals wall infiltration along maize leaf vessels before water refilling - Li, Ke; Wang, Feixiang; Xue, Yanling; Huang, Shiquan; Liu, Zhixuan; Xiao, Tiqiao (Frontiers in Physics, 2025)
Research on the recovery mechanism of embolized vessels requires dynamic and sensitive observations of water refilling. The stable translation of the water/air interface was observed using X-ray absorption and phase contrast imaging. In this study, move contrast X-ray imaging (MCXI) was used to investigate the effect of the microstructure within microvessels on water refilling. Experimental verification using a maize leaf demonstrated that this method was approximately 12 times more sensitive than traditional transmission X-ray imaging. The pre-infiltration of water into the sieve pores of the side wall before water refilling was observed, which provided evidence of a deduction of two-step dynamic equilibrium during water refilling along cavitated vessels and water level rise in dynamic equilibrium instead of translating stably. Several quantitative analyses of the dynamic equilibrium were conducted owing to the high sensitivity of MCXI, making MCXI a promising tool to further investigate the micro-mechanism recovery of embolized vessels.